Can Contracts Signal Social Norms? Experimental Evidence - Anastasia Danilov; Dirk Sliwka (Institute for the Study of Labor (IZA), 2013)
We investigate whether incentive schemes signal social norms and thus affect behavior beyond their direct economic consequences. A principal-agent experiment is studied in which prior to contract choice principals are informed about past actions of other agents and thus have more information about norms of behavior. Compared to a setting with uninformed principals agents exert nearly 50% higher efforts under a fixed wage contract when an informed principal had chosen this contract. Apparently the informed principal's choice signals a norm not to exploit the trust which leads to more trustworthy behavior. This mechanism's robustness is explored in further experiments.
Keywords: D03; C91; D86; 330; social norms; contracts; incentives; signaling; experiments